Total rethink : why entrepreneurs should act like revolutionaries - McCourt, David (Entrepreneur) (Wiley, 2019)
"Rethink your way to a better life In business, and in life, everything is changing fast, apart from how we behave. Our ways of thinking and making decisions have changed little since we lived in agricultural and industrial societies, but the problems we now need to solve are entirely different. It requires a revolution in thinking and behavior to meet the challenges that now face us and avoid disaster we need to totally rethink the model. Part business biography, part business blueprint, Total Rethink explains how this can be done. Successful telecoms entrepreneur David McCourt lays out the reality of the dangerous situation we find ourselves in and suggests solutions which will empower everyone, including business people, politicians, diplomats, and teachers, to repair the damage we have already done, and prepare for the dramatic changes to come. Change the way you think and behave to be a true entrepreneur Understand why incremental change no longer works Move at the speed of the times were living in to keep up Find trusted, effective guidance you can put to practice today Written by a sought-after speaker, businessman, and entrepreneur, the advice inside this book will help you learn to thinkand livelike a revolutionary."--